2007
DOI: 10.1111/j.1478-3231.2007.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐chain amino acids improve insulin resistance in patients with hepatitis C virus‐related liver disease: report of two cases

Abstract: Hepatitis C virus (HCV) infection causes insulin resistance. Because increased insulin resistance is a risk factor for development of hepatocellular carcinoma and reduced long-term survival, insulin resistance is a therapeutic target in patients with HCV infection. Branched-chain amino acids (BCAAs) are not only structural constituents of proteins but they are also considered as regulators of insulin signalling. We first describe two cases suggesting that administration of BCAAs improves insulin resistance ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…In addition to the nutritional role of BCAAs, studies have also evaluated patient QoL based on SF-36 tests (46,47). However, the effect of BCAA supplementation on IR and its association with viral load is less understood (29,30). In the present study, it was demonstrated that treatment with BCAA supplementation decreased IR and improved HR-QoL.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition to the nutritional role of BCAAs, studies have also evaluated patient QoL based on SF-36 tests (46,47). However, the effect of BCAA supplementation on IR and its association with viral load is less understood (29,30). In the present study, it was demonstrated that treatment with BCAA supplementation decreased IR and improved HR-QoL.…”
Section: Discussionsupporting
confidence: 55%
“…A low BCAA/AAA ratio has been documented to reduce the biosynthesis and secretion of albumin in hepatocytes and has also been associated with the prognosis of patients with chronic liver disease (24,25). Oral supplementation with BCAAs may lower blood glucose (26,27) and mitigate CHC (28,29), and in the liver, BCAAs may suppress the expression of G6P and thus the final step of gluconeogenesis (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…The available data indicates that BCAA supplementation raises the serum albumin level and improves the quality of life and survival of patients with decompensated liver cirrhosis. BCAA supplementation has been reported to improve glucose metabolism (11,12). However, mechanisms underlying the efficacy of BCAA supplementation on glucose intolerance in patients with liver cirrhosis have not been completely clarified.…”
Section: Hba1cmentioning
confidence: 99%
“…In addition, several clinical studies have shown that BCAA supplementation improves insulin and glucose tolerance in patients with liver cirrhosis (11,12). However, these short-term studies evaluated the effect of BCAA for less than 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…Aminofeel ® is a commercially available BCAA and zinc-enriched supplement. We previously examined the usefulness of the supplement and demonstrated that it improves insulin resistance, taste sensitivity and adherence to interferon therapy in HCV-infected patients (12)(13)(14)(15)(16). However, it remains unclear whether BCAA and zinc-enriched supplementation improves prognostic factors, including the platelet count, serum albumin levels, homeostasis model assessment for insulin resistance (HOMA-IR) value, serum BTR and zinc levels in HCV-infected patients.…”
Section: Effects Of Branched-chain Amino Acids and Zinc-enriched Nutrmentioning
confidence: 99%